2011
DOI: 10.21608/jfds.2011.81981
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Processing Techniques for Production of Oat and Barley Milks

Abstract: Three trials have been carried out to prepare oat and barley milks with acceptable organoleptic properties and are free of unhealthy and harmful substances. These trails were (A) boiling of intact oat and barley grains after soaking but before disruption, (B) wet toasting of soaked grains before disruption, (C) disruption of soaked grains without heating. Effect of processing conditions (soaking, soaking + heating and soaking + toasting) and the ratio of grains to extracting medium on phytic acid content, % mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(32 reference statements)
1
5
1
Order By: Relevance
“…The yield of OM produced by different treatments ranged from 82.73% (Al) to 91.70% (Sp). These results are in agreement with the results of Salama et al ( 2011 ), who reported that the yields of different OM treatments ranged from 87.6% to 91.25%. However, this study's results were higher than those of Deswal et al ( 2014 ), who reported extraction yield of OM produced by starch liquefaction with α‐amylase treatments ranged from 53.92% to 78.87%.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The yield of OM produced by different treatments ranged from 82.73% (Al) to 91.70% (Sp). These results are in agreement with the results of Salama et al ( 2011 ), who reported that the yields of different OM treatments ranged from 87.6% to 91.25%. However, this study's results were higher than those of Deswal et al ( 2014 ), who reported extraction yield of OM produced by starch liquefaction with α‐amylase treatments ranged from 53.92% to 78.87%.…”
Section: Resultssupporting
confidence: 93%
“…The PEY of OM varied from 63.69% for control treatment to 82.7% for Sp-PA treatments. Salama et al (2011) reported a lower PEY value (43.15%-35.97%) despite higher OM yield, which may be due to the lower protein concentration of oat grains (10.72%) compared to the results of this study. The highest PEY value was achieved by most of the two-stage treatments.…”
Section: Re Sults and Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Similarly, oat milk and barley milk can be prepared using various water ratios, with a 5:1 ratio yielding the best results. 49 However, using a different ratio (12:88 sesame seeds: water) for maximum yield of sesame milk. 50 Beyond its functional properties, permeate holds significant economic potential due to its rich nutritional composition, cost-effectiveness, and versatility in food and beverage applications, unlocking promising avenues for further research and development.…”
Section: Optimum Extraction Conditions and Modelmentioning
confidence: 99%